A remark on Rhoades fixed point theorem for non-self mappings - Ljubomir B. ciric (International Journal of Mathematics and Mathematical Sciences, 1993)
Let X be a Banach space, K a non-empty closed subset of X and T:K→X a mapping satisfying the contractive definition (1.1) below and the condition T(∂K)⫅K. Then T has a unique fixed point in K. This result improves Theorem of Rhoades [1] and generalizes the corresponding theorem of Assad [2].